PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PENDEKATAN KONSTRUKTIVISME PADA MATERI TEOREMA PYTHAGORAS DENGAN BANTUAN ALAT PERAGA - Melkianus Kenda; Uke Ralmugiz; Maria Martini Aba (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
This research aims to develop mathematical student worksheets (LKS) by using the construktivism approach to the pytagorean theorem material with the help of teaching aids in March 2020. The sampling techniquue in this research are purposive sampling. Data coolection techniques using questionnaires, validation sheets and test results. The type of research is used are reseac and development (R&D). Developotment design that is an ADDIE model (Analysis, Design, Development, Implementation, evaluation). Data analysis techniques used are qualitative data consisting of from the analisys of validaty, Practicality, and affectiveness. The results of this study show that the validity of tools based on constructivism approach whit the help of praga tool in RPP was stated to be very valid in review of the results of the validitaion of media experts and material experts whit an average, score of 48,00 tinles in the category xÌ… > 42,06, LKS that was developed was stated to be very valid in view of the results of the validation of the experts with an average score of 48.5 being in the category xÌ… > 42,06, and the props that were developed were stated to be very valid in view of the validation of the media experts, the score 74,00 is in the category xÌ… > 67,21. Practicality results seen froom the questionnaire responses of students declared pratical whith the average number of scores 51,25 in the category 42 < xÌ… â‰¤ 51. The effectiveness results are stated to very effective in terms of student learning outcomes, in the results 84,37% obtained in the â€œvery goodâ€ category P â‰¥ 80. So that it can be concluded that LKS which is developed is valid, pratical and effective in learning mathematics so that it can improve student learning outcomes.